Формування традиційного характеру середовища історичних міст з відтворенням втрачених пам’яток. актуальність, правове та нормативне забезпечення - Мещеряков, В. М.; Meshcheriakov, V. (Видавництво Львівської політехніки, 2018)
Наведено інформацію щодо актуальності теми збереження пам’яток як умови сталого розвитку історичних міст, згадані основні законодавчі та нормативні документи у сфері охорони культурної спадщини, збереження традиційного характеру історичного середовища та відтворення втрачених пам’яток. Аналіз пам’яткоохоронного законодавства, чинної нормативної бази і практики їх застосування в Україні дають підставу вважати за необхідне вдосконалити цю сферу регулювання з огляду на численні порушення умов та обмежень у сфері містобудівної діяльності щодо територій з особливим статусом в історичних містах. Однією з важливих тем формування традиційного характеру історичного середовища є відтво¬рення видатних втрачених об’єктів культурної спадщини з огляду на їх містоутво- рювальну функцію на прикладі відтвореного у 1999-2010 роках Одеського кафедрального Спасо-Преображенського собору.

This article contains information about the importance of preserving the historical objects as a vital condition of a normal development of historical cities. The main legislative and regulatory documents in the fields of protecting of cultural heritage, preserving the traditional character and reconstructing of the lost objects are mentioned. The analysis of the legislation of preserving the objects of cultural heritage, the current regulations and practices of their implementation in Ukraine give grounds for considering importance of improving the regulations with the consideration of numerous violations of conditions and restrictions of urban planning of the cities with the status of historical sites. One of the important topics of the formation of traditional historical character is the re-creation of the lost objects of cultural heritage with the consideration of their role in the city-forming, using as an example the reconstructed in 1999-2010 the Transfiguration Cathedral in Odessa.
The formation of the traditional character of the historical cities with the re-creation of the lost object of cultural heritage - actuality, legislative and regulatory support
Keywords: пам’яткоохоронне законодавство; нормативна база; історичне середовище; відтворення втрачених пам’яток; the legislation and regulations of preserving the objects of cultural heritage; historical environment; the reconstruction of the lost objects; 726.6; 69.059.25